Digital populisms and gender justice: the attack on female activists in cyberspace - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2025)
Focusing on various regions, this collection highlights a rich diversity of feminist activism. The ways feminist movements work, the tools they use, and the outcomes they achieve vary with local dynamics and cultural contexts. In Pakistan, digital activists resist gender-based violence through social media, while in Mexico, protests against femicide resonate globally through digital platforms. In Turkey, feminist video activism builds collective memory, and in Poland, women organize online against abortion bans. This diversity showcases the adaptability, creative strategies, and evolution of feminist movements as they navigate opportunities in the digital age. Feminist activism expresses itself in different voices and methods of resistance across regions, yet all these variations underline a global unity in the fight for equality. This collection demonstrates the expansive, dynamic nature of feminist movements worldwide and examines how local and global struggles intersect.
Keywords: digital populisms; female activists; cyberspace